Evaluation of Adiwiyata Program Management Based on Khalifah Fil Ardh Using The CSE-UCLA Model - Zulfida Aulia Fatimah; Aprilia Nurulita; Annisa Nur Asyiah (Jurnal Isema : Islamic Educational Management, 2026)
MAN 2 Sleman has revived the Adiwiyata Program following a significant decline in both physical and managerial aspects. The researcher used the CSE-UCLA model to evaluate the implementation of the Adiwiyata Program in stages. Data were obtained through observations, interviews, and documentation. Data analysis utilized the model developed Miles, Huberman, and Saldana, which involves data condensation, data presentation, and conclusions. This study concluded that the management of the Adiwiyata Program at MAN 2 Sleman has been implemented, although it has not yet fully aligned with the plan. The researchers concluded  the madrasah has implemented the Adiwiyata Program and applied the concept of khalifah fil ardhl. Furthermore, the summative evaluation phase, it was found the main obstacle was the suboptimal mapping of tasks. This is due to the accreditation tasks which have prevented the Adiwiyata Program from running optimally. These findings have implications for madrasah policies, which are deemed in need improvement regarding the division of responsibilities so that the Adiwiyata Program can run effectively. So, concept of khalifah fil ardh is not only reflected in students’ behavior specifically, their sense of responsibility toward the environment but is also embodied in institutional governance that is oriented toward environmental conservation and sustainability.